2013
DOI: 10.1016/j.apmr.2013.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Description of the Glasgow Outcome Scale-Extended for Individuals in the Traumatic Brain Injury Model Systems National Database: A National Institute on Disability and Rehabilitation Research Traumatic Brain Injury Model Systems Study

Abstract: Individual growth curve analysis is a statistically rigorous approach to describe temporal change with respect to the GOS-E at the individual level for participants within the TBIMS NDB. Results indicated that, for individuals in the TBIMS NDB as a group, functional status as measured by the GOS-E initially improves, plateaus, and then begins to decline. Factors such as age at first GOS-E assessment, race, FIM score at rehabilitation admission, and rehabilitation length of stay were found to influence baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 20 publications
4
44
3
2
Order By: Relevance
“…Patients and their families could use this information to assist in decision-making about long-term care needs and financial plans. 42 Understanding associations between patient or treatment characteristics and recovery patterns could also facilitate clinical decisionmaking throughout rehabilitation and identify targets for intervention 43 . The present study also highlights the value of examining positive outcomes such as positive affect and general adjustment to LLA, which often coexist with negative outcomes following the onset of traumatic experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Patients and their families could use this information to assist in decision-making about long-term care needs and financial plans. 42 Understanding associations between patient or treatment characteristics and recovery patterns could also facilitate clinical decisionmaking throughout rehabilitation and identify targets for intervention 43 . The present study also highlights the value of examining positive outcomes such as positive affect and general adjustment to LLA, which often coexist with negative outcomes following the onset of traumatic experiences.…”
Section: Discussionmentioning
confidence: 99%
“…This study is an extension of the works of Pretz and Dams-O’Connor 18 and Pretz et al 29 in that we focus on how trajectories for those known to be deceased differ from those living. We compared trajectories of deceased and living TBIMS participants for each outcome by constructing a model that (in addition to the covariates used in the previous studies) included living status where 1 = “alive” and 0 = “deceased.” It is important to recognize that not only do covariates act as individual-level descriptors they can also be seen as factors upon which trajectories are conditioned, that is, the covariates serve as statistical controls.…”
Section: Methodsmentioning
confidence: 99%
“…In the TBIMS, the DRS is administered at inpatient rehabilitation admission and discharge, as well as interval follow-ups. For this study only DRS data collected at follow-up were used for 2 reasons: first, we wanted to align temporal measures recorded on the DRS with those captured by the GOS-E. More importantly, previous modeling 18,19 showed that change from admission to discharge greatly overshadows that which occurs during follow-up. Thus, to better understand how change may be related to death among individuals who survive past acute rehabilitation, it was necessary to remove the overpowering influence of change from the rehabilitation process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that this difference may have occurred due to the restricted sample studied and may indicate the need to use more sensitive instruments such as Functional Independence Measure (FIM), the Glasgow Outcome Scale Extended (GOSE), and the Disability Rating Scale (DRS) 23,28,29,30 . Limitations of this study must be borne in mind when interpreting these results and for designing future studies on QOL after TBI.…”
mentioning
confidence: 99%